Representation of iron aerosol size distributions of anthropogenic emissions is critical in evaluating atmospheric soluble iron input to the ocean - M. Liu; M. Liu; H. Matsui; D. S. Hamilton; S. D. Rathod; K. D. Lamb; N. M. Mahowald (Atmospheric Chemistry and Physics)
Atmospheric aerosol deposition acts as a major source of soluble (bioavailable) iron in open ocean regions where it limits phytoplankton growth and primary production. The aerosol size distribution of emitted iron particles, along with particle growth from mixing with other atmospheric components, is an important modulator of its long-range transport potential. There currently exists a large uncertainty in the particle size distribution of iron aerosol, and the extent to which such uncertainty shapes global soluble iron deposition remains unclear. Here, we couple a sophisticated microphysical, size-resolved aerosol model with an iron-speciated and iron-processing module to disentangle the impact of iron emission size distributions on soluble iron input to the ocean, with a focus on anthropogenic combustion and metal smelting sources. We evaluate our model results against a global-scale flight measurement dataset for anthropogenic iron concentration and show that the different representations of iron size distribution upon emission, as adopted in previous studies, introduce a variability in modeled iron concentrations over remote oceans of a factor of 10. Shifting the iron aerosol size distribution toward finer particle sizes (< 1 µm) enables a longer atmospheric lifetime (a doubling), promoting atmospheric processing, which enhances the soluble iron deposition to ocean basins by up to 50 % on an annual basis. The monthly enhancements reach 110 % and 80 % over the Southern Ocean and North Pacific Ocean, respectively. Uniquely, our results highlight that compared with emission flux variability, iron emission size distribution plays an equally important role in regulating soluble iron deposition, especially to the remote oceans. Our new findings can help to interpret inter-model differences in iron deposition estimation and to better quantify the effects of atmospheric nutrient input on marine biogeochemistry, including but not limited to iron and phosphorus.